2019
DOI: 10.1002/ardp.201800381
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel gefitinib‐based derivatives and their anticancer activity

Abstract: Drug latentiation is a process of modifying a drug molecule structurally to improve its binding affinity as well as increasing the drug–receptor interactions and potentiate its therapeutic potential. In the quest for discovering more potent epidermal growth factor receptor (EGFR) inhibitors, gefitinib‐based derivatives were designed by simple structural modification at the secondary amine of gefitinib by N‐alkylation. Three gefitinib derivatives (gefitinib‐NB, ‐NP, and ‐NIP) were synthesized by N‐alkylation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Synthesized compounds were further screened in different cancer cell lines, including MDA-MB-231, to evaluate the cytotoxicity of the new compounds. The results demonstrated a similar effect between experimental and molecular docking analyses, suggesting the important role of gefitinib-based derivatives [70]. Indeed, the in vitro cytotoxicity and antiproliferative activity demonstrated that the derivatives are more potent than gefitinib.…”
Section: Drug Latentiationsupporting
confidence: 67%
See 1 more Smart Citation
“…Synthesized compounds were further screened in different cancer cell lines, including MDA-MB-231, to evaluate the cytotoxicity of the new compounds. The results demonstrated a similar effect between experimental and molecular docking analyses, suggesting the important role of gefitinib-based derivatives [70]. Indeed, the in vitro cytotoxicity and antiproliferative activity demonstrated that the derivatives are more potent than gefitinib.…”
Section: Drug Latentiationsupporting
confidence: 67%
“…Gefitinib is one of the more effective and specific epidermal growth factor receptor (EGFR) inhibitors, which interacts with the adenosine triphosphate (ATP)-binding site of the EGFR tyrosine kinase enzyme. Sharma et al designed three gefitinib-based derivatives to improve the ligand-receptor interaction [70]. Molecular docking studies were also presented for the study of the interactions of the gefitinib derivatives with EGFR, DNA, and BSA.…”
Section: Drug Latentiationmentioning
confidence: 99%
“…Its mechanism of action involves the selective inhibition of EGFR, a growth factor that regulates several critical cellular processes, including cell growth, apoptosis, and angiogenesis [ 18 ]. Upon administration, GEF undergoes extensive hepatic metabolism mediated by cytochrome P450 enzymes, primarily CYP3A4 and, to a lesser extent, CYP3A5 and CYP2D6 enzymes, resulting in the formation of five metabolites [ 19 , 20 ]. Pharmacokinetically, GEF is slowly absorbed after oral treatment, exhibiting a human bioavailability of approximately 60%.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only two therapeutic approaches have been widely used in clinical studies. They are (a) monoclonal antibodies/therapeutic antibodies (MAbs)—etuximab (Erbitux®), trastuzumab (Herceptin®), Osimertinib [ 14 ], Nimotuzumab [ 15 ], panitumumab (Vectibix®) [ 16 ], and Necitumumab [ 17 ]; (b) small-molecule inhibitors of EGFR tyrosine kinase (EGFR-TKI)—first generation: ZD 1839 (Iressa®, Gefitinib), Erlotinib (Tarceva®), and Crizotinib (Xalkori®) [ 6 , 10 ]; second generation: Lapatinib (Tyverb®), Afatinib (Gilotrif®), and Dacomitinib [ 18 ]. Monoclonal antibodies exert their action by blocking the ligand from binding to the extracellular area of the receptor.…”
Section: Introductionmentioning
confidence: 99%